A study on factors influencing employee engagement among Gen Y employees in McDonald's Klang Valley - Ismail, Juniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The purpose of this study to investigate the factors influencing employee engagement among Gen Y at McDonald’s in Klang Valley. The primary objective of this paper is to determine the relationships between the employee engagement factors (leadership, communication, rewards and recognition, work-life balance and training and development) among Gen Y at McDonald’s in Klang Valley. A qualitative and quantitative study was deployed by the researcher. This research consists of semi-structured interview with the representive from headquarter and restaurant manager. Meanwhile, self-administered questionnaire is used to collect information on employee engagement among the Gen Y at the restaurant branch. The findings analysis indicates the factors of engagement have correlations with employee engagement. However, the variables that had major impact were leadership and communication. A special focus and effort is required on the least significant factors by promoting a healthy work-life balance for its Gen Y employees, interesting approach in training into a ‘learning playground’ and flexible salary payments for employees.